Fatores associados à espiritualidade e religiosidade de idosos cuidadores e não cuidadores - Souza, Érica Nestor (Universidade Federal de São Carlos, 2020)
For the elderly, spirituality and religiosity can be a resource to face the adversities of the aging process. For the elderly caregivers, emotional support tools that assist in the performance of care activities. The objective of this research was to analyze which sociodemographic factors, emotional aspects, mental health and social support are associated with the spirituality and religiosity of elderly caregivers and non-caregivers. This is a quantitative, cross-sectional, observational and exploratory study with a comparison group carried out with elderly caregivers (n = 85) and non-caregivers (n = 84) registered at Family Health Units in a city in the interior of São Paulo. The instruments for data collection were: sociodemographic and care characterization; Pinto e Pais-Ribeiro Spirituality Scale (EEPP-R); Duke's Religious Scale (DUREL); Addenbrooke's Cognitive Exam - Revised (ACE-R); Perceived Stress Scale (PSS); Geriatric Depression Scale (GDS); Lawton and Brody scale and Social Support Scale MOS. Used to analyze simple and multiple linear regression with Stepwise selection criteria and significance index of p≤0.05. All ethical precepts were followed. As for the results, in both groups, there was a prevalence of females, the average age was 69.6 years in caregivers and 70.8 in non-caregivers. As for religion, the prevalence in both groups was Catholic. For caregivers, the average score on the evaluation scales was 3.5 on the global EEPP-R; 2.8 of organizational religiosity (RO), 1.6 non-organizational religiosity (RNO) and 4.4 intrinsic religiosity (IR); 62.8 in the ACE-R; 3.7 in the GDS; 18.6 in the PSS; 54.1% independent on the Lawton and Brody scale and highest average 89.8 on the MOS affective support. As for non-caregivers, 3.4 in the global EEPP-R; 2.5 RO, 1.8 RNO and 4.2 RI; 62.0 in the ACE-R; 3.6 in the GDS; 16.7 in the PSS; 61.4% with partial dependence on the Lawton and Brody scale and a higher average of 91.6 in the MOS emotional support. In conclusion in the analysis of multiple linear regression, the factors associated with a higher spirituality score in elderly caregivers were: having greater material support, without depressive symptoms, receiving enough affective / emotional help, being female and having a lot of satisfaction with life. For non-caregivers, a higher spirituality score was related to a lot of satisfaction with life, being younger, with cognitive impairment and with independence in instrumental activities of daily living. A higher religiosity score in elderly caregivers was associated with being Catholic, without a partner and male, and for non-caregivers they were Catholic, with depressive symptoms, being little satisfied with life and having greater family income.
Factors associated with spirituality and religiosity of elderly caregivers and non-caregivers
Keywords: Idosos; Cuidadores; Espiritualidade; Religião; Enfermagem geriátrica; Elderly; Caregivers; Spirituality; Religion; Geriatric nursing; CIENCIAS DA SAUDE::ENFERMAGEM